PENGARUH PELATIHAN DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA MELALUI KINERJA PADA UMKM YANG BERGERAK DI SEKTOR MAKANAN DAN MINUMAN SE-KABUPATEN INDRAGIRI HULU - Tanty Veronica; Marzolina Marzolina; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of training and organizational culture to work productivity through performance at umkm in the food and beverage sector in Indragiri Hulu District, totaling 8 UMKM with 55 employees. Primary data was collected by questionnaire as an instrument to prove the result of the research, tp test the hypothesis in this study is using path analysiis with SPSS (Statistical Program For Social Sciences). The sampling technique is a method that has been selected cencus (8 UMKM with 55 employees). The result showed that : 1). There is a positive and significant effect of training on the performance of the UMKM in the food and beverage sector in Indragiri Hulu District. 2). There is a positive and significant effect of organizational culture on the performance. 3) There is a positive and significant effect of training on the work productivity. 4) There is a positive and significant effect of organizational culture on the work productivity 5) There is a positive and significant effect of training on the work productivity through performance. 6) There is a positive and significant effect of organizational culture on the work productivity through performance. 7) There is a positive and significant effect of performance on the work productivity.Keywords : Training, Organizational Culture, Performance, Work Productivity